A common conserved peptide harboring predicted T and B cell epitopes in domain III of envelope protein of Japanese Encephalitis Virus and West Nile Virus for potential use in epitope based vaccines. (August 2019) - Slathia, Parvez Singh; Sharma, Preeti
Highlights: Peptide "TPVGRLVTVNPFV" common in envelope protein of WNV and JEV. Peptide contains predicted T and B cell epitopes. Peptide showed binding in the groove of HLA-A0201. Database comparisons showed peptide to be non-toxic, non-allergic and stable in nature. Abstract: Japanese encephalitis virus (JEV) and West Nile virus (WNV) are two major mosquito borne flaviviruses belonging to same serocomplex. JEV is transmitted by Culex mosquitoes and the reservoir host for the virus is pigs and/or water birds. WNV is also transmitted by Culex mosquitoes and reservoir host in this case is birds. It can also be transmitted through contact with other infected animals, their blood, or other tissues. The envelope protein of these viruses is the major source of epitopes and provides protective immunity. Bioinformatics tools were used to identify conserved epitopes in the envelope protein of these viruses. A conserved peptide "TPVGRLVTVNPFV" present in both the viruses containing predicted T and B cell epitopes was found. The model of one of the predicted epitope was generated and upon docking it bound in the groove of HLA-A0201 Class I MHC molecule. Further, it was amenable to proteasomal cleavage enhancing its chances of processing by cytosolic pathway. The peptide was found to be non toxic, non allergenic and stable in mammalian cells based on database search. The population coverage was pan world and nearly 70% identity of the peptide was found in the Zika virus envelope protein. The peptide was located in the domain III of envelope protein which is the exposed domain therefore B cell receptors may recognize this peptide easily. The conserved peptide containing T and B cell epitopes can have future application for designing epitope based vaccines for both JEV and WNV.